Post-exercise Recovery Methods Focus on Young Soccer Players: A Systematic Review - Calleja-González, Julio; Mielgo-Ayuso, Juan; Miguel-Ortega, Álvaro; Marqués-Jiménez, Diego; Del Valle, Miguel; Ostojic, Sergej M.; Sampaio, Jaime; Terrados, Nicolás; Refoyo, Ignacio (Frontiers in Physiology, 2021)
Background: In soccer, training prescription for youth soccer players should consider the specific demands of competitive match play. Further, it is usual to play several competitive matches with insufficient recovery. To facilitate adequate recovery, it is necessary to understand the type of fatigue induced mechanisms. Besides, young players present a differential physiological and anatomical characteristic inside the maturation process. The purpose of this systematic review was to examine the current recovery methods in youth soccer players to provide a source of support to sport practitioners Methodoloy: A structured search was carried out following the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines until July 2- 2019, using the next data bases: WOS, Collaboration Database, Cochrane Library, Evidence Database (PEDro), Evidence Based Medicine (EBM) Search review, EMBASE, National Guidelines and Scopus. There were filters applied to the players’ age and soccer. Results: A total of 364 articles were obtained in the initial search. After inclusion and exclusion criteria the final sample was 8 articles focus on recovery in young players. Conclusions/Significance: The combination of cold-water immersion plus active recovery may be effective after match, but only cold-water immersion reduces the perception of general fatigue and leg soreness between matches. The Spa treatment is questionable. Whole-body vibration with a traditional cool-down protocol reduces the perceived muscle pain and seems to hasten the recovery of lower-limb explosive force. The passive recovery is better for subjective fatigue estimation. In contrast, the estatic streching is not a beneficial recovery option for elite youth soccer players.